Clinical Efficacy and Safety of Hyperthermic Intraperitoneal Chemotherapy in Colorectal Cancer Patients at High Risk of Peritoneal Carcinomatosis: A Systematic Review and Meta-Analysis - Zhao, Peng-yue; Hu, Shi-dong; Li, Yu-xuan; Yao, Ren-qi; Ren, Chao; He, Chang-zheng; Li, Song-yan; Wang, Yu-feng; Yao, Yong-ming; Huang, Xiao-hui; Du, Xiao-hui (Frontiers in Surgery, 2020)
Background: Hyperthermic intraperitoneal chemotherapy (HIPEC) is an effective measure for improving the prognosis of colorectal cancer (CRC) patients with peritoneal carcinomatosis (PC). However, the role of HIPEC in CRC patients at high risk of PC remains controversial. The aim of the current systematic review and meta-analysis was to evaluate the clinical efficacy and safety of HIPEC in CRC patients at high risk of PC. Methods: We performed a systematic search of PubMed, Embase, Cochrane Library and other online databases up to July 30, 2020. The clinical data, including overall survival, disease free survival, peritoneal metastasis rate and postoperative adverse reaction were screened and analyzed after data extraction. Risk ratios (RRs) were applied to analyze these dichotomous outcomes with a random effects model. Results: A total of 6 available clinical studies involving 603 patients were finally included. CRC patients at high risk of PC who proactively underwent HIPEC treatment showed a significantly reduced peritoneal metastasis rate (RR: 0.41, 95% CI: 0.21-0.83, P=0.01; I2=58%) compared to that in similarly high-risk CRC patients who did not receive HIPEC treatment. However, in terms of overall survival (RR: 1.13, 95% CI: 0.97-1.33, P=0.12; I2=77%), disease-free survival (RR: 1.10, 95% CI: 0.75-1.59, P=0.63; I2=53%), progression free survival (RR: 1.85, 95% CI: 0.48-7.14, P=0.37; I2=93%) and postoperative adverse reactions (RR: 0.1.07, 95% CI: 0.36-3.15, P=0.90; I2=78%), there was no significant difference between the HIPEC treatment and control groups. Conclusions: Proactive HIPEC treatment did not show the expected clinical efficacy in prolonging the overall survival time, disease-free survival time and progression-free survival time of CRC patients at high risk of PC. However, the preemptive administration of HIPEC was associated with a reduced peritoneal metastasis rate and did not cause additional postoperative adverse effects.